2005
DOI: 10.1248/cpb.53.714
|View full text |Cite
|
Sign up to set email alerts
|

Non-reductive Scavenging of 1,1-Diphenyl-2-picrylhydrazyl (DPPH) by Peroxyradical: A Useful Method for Quantitative Analysis of Peroxyradical

Abstract: For quantitative investigations of hydrogen-radical donation, stable radicals have the advantage that their concentrations are readily and directly measurable. Among them a stable free radical 1,1-diphenyl-2-picrylhydrazyl (DPPH) 1) was investigated as a reactive hydrogen acceptor 2) and further found to be useful for the antioxidant determination.3) Since then DPPH has been mainly used to examine radical scavenging activity of antioxidative vitamins and polyhydroxy aromatic compounds 4,5) based on the reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 17 publications
(14 reference statements)
1
22
0
3
Order By: Relevance
“…(cation radical) free radical. A wide variety of in vitro methods used to assess radical scavenging ability of certain agents from natural and synthetic source [30]. It can be observed that the content of flavonoids and tannoid compounds of EFE could be responsible for the radical scavenging activity.…”
Section: Discussionmentioning
confidence: 99%
“…(cation radical) free radical. A wide variety of in vitro methods used to assess radical scavenging ability of certain agents from natural and synthetic source [30]. It can be observed that the content of flavonoids and tannoid compounds of EFE could be responsible for the radical scavenging activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have found that a stable radical 1,1-diphenyl-2-picrylhydrazyl (DPPH) is a useful agent for the quantitative measurement of peroxyradicals. 7) In brief, as shown in Fig. 1, non-reductive DPPHscavenging by peroxyradical is quantitatively determined by ESR analysis.…”
mentioning
confidence: 99%
“…In this study, we report that peroxyradical(s) was proved to be present in the gas-phase cigarette smoke using the method described in our previous study. 7) Several studies have been conducted to inactivate free radicals from cigarette smoke by using antioxidants. [8][9][10][11] As indicated in the previous study, 10) antioxidants used should necessarily be effective against broad range of free radical species, be heat resistant, nonvolatile and display high affinity to the filter.…”
mentioning
confidence: 99%
“…a free radical scavenging antioxidant, the absorption strength is decreased and the resulting decolorization is stoichiometric with respect to the number of electrons captured. It has been found that DPPH * can oxidize cysteine, glutathione, ascorbic acid, tocopherol and polyhydroxy aromatic compounds [56]. ABTS*+produce more powerful free radicals than DPPH * radicals and the reactions with ABTS *+ radicals involve a single electron transfer process [57].…”
Section: Discussionmentioning
confidence: 99%